Octopus Fishing and New Information on Ecology and Fishing of the Shallow-Water Octopus Callistoctopus furvus (Gould, 1852) Based on the Local Ecological Knowledge of Octopus Fishers in the Marine Ecoregions of Brazil - Jesus, Manuella Dultra; Zapelini, Cleverson; Santana, Romário Oliveira de; Schiavetti, Alexandre (Frontiers in Ecology and Evolution, 2022)
Studies that compile local ecological knowledge (LEK) on some of the various species of living beings observe biological data and are notably fundamental for effectively managing fisheries, supporting management strategies for protected areas, species conservation, and other factors. In this study, ethnoecological approaches were used to focus on the octopus Callistoctopus furvus (Gould, 1852), recently re-described and re-presented to the academic community more than a century after its discovery. The LEK of octopus fishers from different marine ecoregions of Brazil was compared to identify the distribution limits of the species along the Brazilian coast. Semi-structured interviews were conducted in 16 municipalities across four marine ecoregions located between the states of Ceará (northern limit) and Santa Catarina (southern limit), between March 2018 and August 2019. The results of the 187 interviews indicated a traditionality of fishing among artisanal octopus fishers, who are mostly men, although some are women who also share information on the fishing of C. furvus and hold leadership positions in the fishing colony. Cronbach's alpha was used to analyze reliability of the form used in the interviews. A logistic regression model with binomial distribution was used to assess whether the probability of capturing the “eastern octopus” was associated with some of the interview variables. A cluster analysis based only on the respondents who caught the "eastern octopus" indicated the formation of groups and revealed greater dissimilarities among the fishers from the southeastern marine ecoregion of Brazil due to the fishing method used in the region. Heat maps showed that most of the information on the species was obtained in the eastern marine ecoregion of Brazil. The occurrence of the” eastern octopus" was recorded in all the studied Brazilian marine ecoregions. Moreover, this study revealed the relevant contribution of fishers' knowledge to the distribution diagnosis of species with scarce scientific information.